In-situ phase fractions for oil and water occupied in pipe channel - Hussain, Siti Aslina; Mustapa Kamal, Siti Mazlina (Federation of Engineering Institutions of Islamic Countries, 2006)
Using of traversing beam gamma densitometer measurement for the phase fractions distribution of a mixture of water and kerosene namely EXXSOL-D80 was achieved experimentally into 25.4 mm ID in a horizontal pipe channel. The phase fractions distribution was determined with the beam being traversed in three directions for examples 00, 450 and 900 of the vertical line passing through the axis of the pipe channel. Measurements were made at three positions spaced along the 9.7 m test section length (1.0 m, 5.85 m and 7.72 m along the horizontal pipe channel) with three input water fractions of 40%, 46% and 60%. The measurements were done in Two-phase Oil Water Experimental Rig (TOWER) facility. This facility allows the two fluids to be fed to the test section before they separated and returned once more to the test line. The flow developed naturally from an initial stratified flow in which the oil and water were introduced separately at the top and the bottom of the test section respectively. The flows were such that the liquids were fully inter-dispersed by the end of the test section. The phase fractions distribution was shown to be homogeneously mixed near to the outlet of the test section. The mean hold-up was found to depend on the input phase fraction, the mixture velocity and the position along the test section.